ANALISIS EFISIENSI DENGAN MENGGUNAKAN METODE DEA (DATA ENVELOPMENT ANALYSIS) DI TPI (TEMPAT PELELANGAN IKAN) DI PROVINSI BANTEN - Ipan Hilmawan (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2021)
Fish Auction Place is part of functional facility of Fishery Port which acts as center of marketing activity or fish transaction. In marketing fish catch fishers, Fish Auction Place have an important role to create healthy market through auction activities that are useful to maintain the stability of fish prices and maintain the quality of fish catches of fishermen, can be interpreted that the Fish Auction Place needs to be managed with the best to be able to become the main choice for fishermen in marketing their catch fish and the achievement of the benefits of activities at the Fish Auction Place optimally for the parties involved, whether fishermen, fish auctioneers, fish baskets, and fish buyers. This study aims to determine the technical efficiency level of Fish Auction Place in Banten Province and the techniques used in sampling are purposive sampling with quantity of 9 units, namely Cituis Fish Auction Place, Kronjo, Tanjung Pasir, Terate, Karangantu, Labuan 1, Labuan 2, Labuan 3 and Binuangeun, and using 7 input variables that is, Length of Landing Base (m), Area of ​​Auction Floor (m²), Number of Fishing Equipment (unit), Number of Ships (unit), Number of TPI Personnel, Number of Fishermen (person), and Number of Bakul (person), and use 2 variable output that is, Raman Value (Rp), and Share Omzet TPI (%). Data analysis technique used is non-parametric frontier approach Data Envelopment Analysis ¬ to know the efficiency value of 9 Place of Fish Auction Place in Banten Province which calculated by using software tool of Banxia Frontier Analysis with result of calculation that there are 8 spot of Fish Auction with efficiency score 100 % that is, Binuangeun, Karangantu, Kronjo, Labuan 1, Labuan 2, Labuan 3, Tanjung Pasir, and Terate or can be said to have achieved efficiently and 1 Fish Auction Place with efficiency score 42,8% that is, Cituis or can be said not yet reached efficiently, and some improvements in inputs and outputs can be achieved to achieve a 100% efficiency score or can be said to be efficient based on or in accordance with the value of potential improvement generated in the calculation of efficiency using the Banxia Frontier Analysis software